2012
DOI: 10.1007/s00227-012-2036-0
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Hyas araneus zoea I larvae to elevated seawater PCO2 despite elevated metabolic costs

Abstract: Early life stages of marine crustaceans respond sensitively to elevated seawater PCO 2 . However, the underlying physiological mechanisms have not been studied well. We therefore investigated the effects of elevated seawater PCO 2 on oxygen consumption, dry weight, elemental composition, median developmental time (MDT) and mortality in zoea I larvae of the spider crab Hyas araneus (Svalbard 79°N/11°E; collection, May 2009; hatch, December 2009). At the time of moulting, oxygen consumption rate had reached a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 46 publications
3
12
0
Order By: Relevance
“…Our results showed that OA has a mixed effect on swimming crabs, with increased survival and retarded growth. The negative effect on growth is in line with findings published for other crab species such as larvae of H. araneus ( Walther et al, 2010 ; Schiffer et al, 2013 , 2014 ; Wang et al, 2018 ), Paralithodes camtschaticus , and Chionoecetes bairdi ( Long et al, 2013a , b ), as well as embryos of Petrolisthes cinctipes ( Carter et al, 2013 ; Ceballos-Osuna et al, 2013 ). Such a consensus between studies performed on different species, at different stages of development and with p CO 2 ranging from 710 to 3100 μatm, strongly supports crab sensitivity to OA.…”
Section: Discussionsupporting
confidence: 89%
“…Our results showed that OA has a mixed effect on swimming crabs, with increased survival and retarded growth. The negative effect on growth is in line with findings published for other crab species such as larvae of H. araneus ( Walther et al, 2010 ; Schiffer et al, 2013 , 2014 ; Wang et al, 2018 ), Paralithodes camtschaticus , and Chionoecetes bairdi ( Long et al, 2013a , b ), as well as embryos of Petrolisthes cinctipes ( Carter et al, 2013 ; Ceballos-Osuna et al, 2013 ). Such a consensus between studies performed on different species, at different stages of development and with p CO 2 ranging from 710 to 3100 μatm, strongly supports crab sensitivity to OA.…”
Section: Discussionsupporting
confidence: 89%
“…In our experiment, the SMR was 10–20 μmol O 2 kg -1 min -1 , which was similar to previous results for C. pagurus (8–19, Naylor et al, 1997 ). Increased metabolic rates under elevated pCO 2 conditions were observed in crab ( Schiffer et al, 2013 ) and other invertebrates ( Lannig et al, 2010 ; Thomsen and Melzner, 2010 ; Parker et al, 2012 ), implying these species have an ability to at least partially compensate for the increased energy costs of acidosis ( Gibson et al, 2012 ). However, some opposite studies have shown that oxygen consumption in Metacarcinus magister acclimated to high pCO 2 for 7 days was significantly decreased ( Hans et al, 2014 ), indicating that M. magister undergoes partial metabolic depression under elevated pCO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies of physiological responses of crabs exposed to elevated pCO 2 ( Pane and Barry, 2007 ; Spicer et al, 2007 ; Fehsenfeld et al, 2011 ) have identified a wide range of responses ( Kroeker et al, 2010 ). High CO 2 has been reported to negatively impact various physiological processes, including growth ( Walther et al, 2010 ), survival ( Melzner et al, 2009 ), development ( Walther et al, 2010 ; Schiffer et al, 2013 ), immune response ( Meseck et al, 2016 ), chemoreception ( de la Haye et al, 2012 ), and swimming performance ( Dissanayake and Ishimatsu, 2011 ). The most immediate physiological responses to ocean acidification (OA) in marine crustaceans are best described by acid–base adjustments ( Pane and Barry, 2007 ; Pörtner et al, 2010 ; Whiteley, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additive effects of increased temperature and CO 2 were recorded for survival, development, growth, and lipid synthesis of larvae and juveniles of Northwest Atlantic bivalves [ 17 ]. At ambient temperature, elevated CO 2 (3100 ppm) resulted in increased mortality and prolonged developmental time accompanied with a decrease in oxygen consumption rates of developing zoea I of Hyas araneus , when they were exposed to CO 2 during their embryonic development [ 18 , 19 ]. So far, there is limited data available on the thermal tolerance of larval stages exposed to elevated seawater P CO 2 .…”
Section: Introductionmentioning
confidence: 99%